Perception and Social Influence of Sports Betting Advertisements on Gambling Behaviour of Youths in Makurdi Metropolis: An Assessment - Aondowase, Saawuan; Udoudom, Uduak Imoh; Pam, Christiana Chundung (Darul Yasin Al Sys, 2023)
This study assessed the perception of sports betting advertisements and influence on the gambling behaviour of youths in Makurdi metropolis. Survey research method was adopted for the study, while questionnaire was employed as instrument for data collection. A sample size of three hundred and fifty three (353) was statistically drawn using Taro Yamane’s sample determination formula. Data from the study were presented in tables using simple percentages. Findings revealed that youths in Makurdi perceived sports betting advertisements as part of sports which hsas no harmful influence on them thereby justifying their regular participation in sports betting activities. The study further found that sports betting advertisements have significant influence on Makurdi youths by inducing them to bet more on sports as well as make them nurture intentions to consume sports betting products. The ubiquity of sports betting advertisements, the pressure from peers and the proliferation of bet shops have been found to be the cardinal determinants to the surge of sports betting activities among youths in Makurdi metropolis. The study recommended among others that the current regulatory systems for gambling advertising are ineffective. Urgent restrictions are needed across a range of media channels to prevent exposure to promotions that may encourage young people’s interest and involvement in sports gambling; and that, APCON should continually evaluate existing and newly implemented advertising techniques to ensure that promotions of sports betting products or contents are not unduly targeting youths or increasing the risk of gambling among youths.